Strategi Pengembangan Badan Usaha Milik Desa (BUMDes) Sumber Mulia di Desa Purwareja Kabupaten Lamandau - Iyan Iyan; Asriansyah S Mawung; Bambang Mantikei (Journal of Environment and Management, 2020)
Village is the lowest unit in the state administration structure in Indonesia. The central government has been providing Village Funds program, sourced from State Budget, in order to support village development. Village-owned enterprises or BUMDes is a crucial point to comes up village initiatives into reality. The purpose of this research is to identify the supporting and inhibiting factors as well as to analyze the development strategy of BUMDes Sumber Mulia in Sematu Jaya Sub-District, Lamandau Regency, in managing and utilizing its assets. Data were collected through interview, observation and documentation, then analyzed using reduction techniques and data presentation, before, conclusion drawing. SWOT method was used to analyze the BUMDes development strategies as a basis fo formulate the priority one. The results showed that the top priority alternative for the development of BUMDes Sumber Mulia is Strategy III (with a TAS value of 6.75), namely being a distributor of fertilizer and pharmaceutical. The second priority is the Strategy I (TAS value equal to 6.21), namely creating a new business, and the third priority is a strategy II (TAS value of 5.53), namely improving quality of human resources.